Pemanfaatan Media Pembelajaran Audio Visual dalam Mengembangkan Motivasi Belajar Siswa Pada Materi Pelajaran IPS Terpadu - Agnes Avenia Br Barus; Erni Susilawati Purba; Jumay Eferta Tarigan; Jacob Kuntuy; Andi Taufiq Umar (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Audio visual learning is a learning medium that utilizes image elements. The aim of this research was to find out whether the audio visual learning method implemented at SMA N 18 Medan was able to develop and increase students' learning motivation in Integrated Social Sciences lesson material. In this research the author uses a qualitative approach. The data collection techniques used are observation, interviews and documentation, with this method the results obtained are valid and can be tested. The results found from this research are that the use of audio-visual learning media at SMA N 18 Medan provides positive impact and is able to develop and increase students' motivation in participating in learning in the classroom, and planning for the use of learning media has been carried out optimally by the teacher. The conclusion is that the use of audio-visual learning media has a positive impact and has an important role in achieving learning goals and has great potential in increasing student learning motivation.